Literature Review: Role of Vitamin D in Diabetic Foot Ulcer Wound Healing - Kemas Dahlan; Irfanuddin; Krisna Murti; Akhmadu Muradi (Postgraduate, University of Mataram, 2023)
DFU is a common consequence of DM. Vitamin D has multiple positive effects on DFU. Search data from; Google Scholar, Science Direct, Elsevier, EBSCO, Medline and PubMed. Publication at least ten years (2013 until 2022). Inclusion criteria; full paper in English, Study about vitamin D and DFU in human, exclusion criteria; animal model and invitro study. Results; 27 journals; Seven Randomized Controlled Trial. Vitamin D phase on DFU which one substantially smaller. Severe vitamin D insufficiency known with significance linked for an elevated risk of DFU. Vitamin D supplementation can prevent or improve diabetic foot complications